Teachers' Perceptions of Islamic Leadership Values Implementation in Secondary Schools During Management Reform - Mawardi Mawardi; Aan Komariah; Sururi Sururi; Suryadi Suryadi; Eka Prihatin (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: This phenomenological study explored teacher perceptions of Islamic leadership values implementation in Islamic-based secondary schools (MTS) during management reform. Research involved ten teachers from three MTS in Pandeglang, Banten, Indonesia. Data were collected through semi-structured interviews (60-90 minutes) and analyzed using reflexive thematic analysis with ATLAS.ti software. The study examined five key dimensions: exemplary leadership (qudwah hasanah), interpersonal relations (ukhuwah Islamiyah), participatory decision-making (shura), management reform effectiveness, and teacher competency development. Findings reveal that teachers perceive Islamic leadership as a holistic integration of spiritual and operational dimensions. Notably, management reform synergizes with Islamic values when implemented gradually with cultural sensitivity, enhancing both operational efficiency and spiritual purposes (dakwah and tarbiyah). Teacher development integrates formal training with mentoring and peer support, fostering simultaneous professional competency and spiritual growth. This study provides empirical evidence from teacher perspectives—frontline implementers—demonstrating that modern management innovation and Islamic principles can effectively align in educational practice. Keywords: Islamic leadership; teacher perceptions; management reform; secondary schools; qudwah hasanah